RISK FACTOR ASSESSMENT FOR ACNE VULGARIS IN HUMAN AND IMPLICATIONS FOR PUBLIC HEALTH INTERVENTIONS IN NORTH CENTRAL INDIA: A SURVEY-BASED STUDY - Qidwai, Afifa; Pandey, Manisha; Shukla, Shashi Kant; Pandey, Anand; Kumar, Rajesh; Dikshit, Anupam (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Background: Acne vulgaris is a very common dermatological problem of adolescence since the time immemorial. However, it is neither life threatening nor is a physical disability, but acne affects social and psychological functioning. Acne vulgaris is multifactorial, apart from basic factor of hormonal change and bacterial outbreak; there are several other factors that may influence the prevalence of acne. Methods: In the present study, populations were assessed for influence of various factors on acne prevalence. This cross-sectional study was a population based field study intending to discern the factors that influence the prevalence of acne in adolescents. The study carried out from April 2016 to October 2016 in north central India. For this survey, questionnaires were design to cover all the required information regarding occurrence of acne that include factors like gender, age, skin type, complexion, season of occurrence, dietary habit etc. Results: Acne vulgaris appears to be influenced by gender, age, seasonal variations, breakout area, complexion, skin types and dietary habits. Further, the influence of dietary habit on acne, by the consumption of dairy products or high-carbon diet has also been evaluated. Apart from depicting the vulnerable range of age (p=0.003288), sensitivity on various skin types (p=0.00039) and complexion (p=0.001355) on the basis of gender; This Field study on Acne Vulgaris, also reveals that the season has inordinate role in acne pervasiveness (p=0.115731). Conclusion: This study is helpful in categorizing the risk factors and evidencing the afflictions of acne in population thus, contributing health care planning.Â  Â 